Z DZIEJÓW FRANCUSKIEGO MODELU „LA PUBLICITÉ FONCIÈRE” - Blajer, Paweł (Zeszyty Prawnicze, 2016)
Some Aspects of the History of the French ‘Publicité Foncière’ System Summary In this article the author applies a broad historical perspective to describe the origins and evolution of the French publicité foncière system as an instrument for the publicity (record-keeping) of property transactions. To achieve this aim he divides the article into particular chapters as required by the nature of the subject. According to the systematics adopted in the French literature, the history of the publicité foncière system is divided into three fundamental periods, which are discussed in three separate chapters. These three main periods are the age of l’ancien droit (viz. French law prior to the Revolution), the legislation of the Revolutionary period and Napoleonic Code; the period since the mortgage law of 1855. The research conducted in the article’s three main chapters enables the author to identify the factors which have determined the main trend in the history of the French method of land registration, and the extent to which it has influenced Polish regulations on land registration.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" /><br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />